Interfacing participation in citizen science projects with conversational agents - Portela, Manuel (Human Computation, 2021)
This paper assesses the use of conversational agents (chatbots) as an interface to enhance communication with participants in citizen science projects. After developing a study of the engagement and motivations to interact with chatbots, we explored our results. We based our analysis on the current needs exposed in citizen science literature to assess the opportunities. We found that chatbots are great communication platforms that can help to engage participants as an all-in-one interface. Chatbots can benefit projects in reducing the need for developing an exclusive app while it can be deployed on several platforms. Finally, we establish design suggestions to help citizen science practitioners to incorporate such platforms to new projects. We encourage the development of more advanced interfaces through the incorporation of Machine Learning to several processes.